AUTOMATED FLOW-INJECTION TECHNIQUE FOR USE IN DISSOLUTION STUDIES OF SUSTAINED-RELEASE FORMULATIONS - APPLICATION TO IRON(II) FORMULATIONS - Georgiou, C.A.; Valsami, GN; Macheras, PE; Koupparis, MA (JOURNAL OF PHARMACEUTICAL AND BIOMEDICAL ANALYSIS, 1994)
The application of flow-injection analysis (FIA) to automated dissolution studies of sustained-release formulations is described. The long-term stability of the dissolution-FIA analyser was checked during unattended operation for 42 h. The construction of multiple calibration curves with the so-called electronic dilution FIA procedure was used to extend the linear range of the determination. The computer-controlled FIA system and the principles of associated software are described and applied to dissolution studies of sustained-release formulations of iron(II) using its sensitive reaction with the colour reagent, ferrozine. The extended linear range of the determination is 1-130 ppm iron(II) and the precision (RSD) better than 3% (n = 3).
Keywords: DISSOLUTION TESTING AUTOMATION; FERROZINE; FLOW-INJECTION ANALYSIS; IRON DETERMINATION IN DRUG FORMULATIONS; SUSTAINED-RELEASE FORMULATIONS